Collaterals' issue in RAHN scheme and conventional pawn broking: a literature study - Md Harun, Ahmad Syahir; Haneef, Sayed Sikandar Shah; Awang, Abdul Bari (2017)
Rahn or pawn broking is one of contracts that Islam allows to assist people when they are short of money to ease their financial difficulty. Obviously, in Islamic teaching, collaterals other than gold and silver are allowed but the collaterals' variation in Islamic institutions in Malaysia do not apply this teaching in their system as compared to conventional pawn broking where people are more attracted to them since they offer other collaterals such as lands, houses, cars and electronic devices. Therefore, this study will show the necessity of diversifying collateral in rahn scheme in Islamic Institutions in Malaysia. This study is important to show people that Islamic revelation is relevant to today's developments which ease people in all aspect especially economy. This study will analyze the relevant previous researches in rahn as a literature study.